Development and Characterization of Microwave Absorber Composite Material - Al-Mattarneh, Hashem (International Journal of Engineering and Technology, 2018)
The rapid development of electronic systems and telecommunications has resulted in a growing and intense interest in microwave electromagnetic absorber technology and microwave absorbing composite material. This research was conducted to develop microwave absorber composites called thermoplastic natural rubber barium ferrite (TPNR-BF). The composite was characterized by determination of its physical, mechanical, magnetic and microwave properties. TPNR-BF with the fine particles barium ferrite filler content of 0-20% by weight were prepared using melt blending method. The microwave electromagnetic properties were measured using free-space microwave non-destructive testing system (MNDTS) in the frequency range of 7-13 GHz. The mechanical and Magnetic properties of the thermoplastic natural rubber-barium ferrite were also measured using Magnetometer. The effects of the different percentage of filler content on the mechanical and microwave properties of the composites have been evaluated. Both microwave dielectric constant and the reflection coefficient of TPNR-BF increase with increasing frequency and filler content while transmission coefficient decreases with increasing filler content which indicates that the composite absorbs more microwave energy by the filler. Barium ferrite contents show an inverse relation with the mechanical properties such as tensile strength and stiffness. MNDTS shows excellent capability for advanced characterization of a microwave composite material.